Management of nonarthritic meniscal tears: a qualitative, patient-centered assessment of decision making. Issue 4 (July 2020) - Nelson, Patrick; Bhatt, Surabhi; Terry, Michael; Tjong, Vehniah
Abstract : Background: Meniscal lesions are the most common intraarticular knee injury. Treatment involves a decision for conservative management or surgery. Recent literature has demonstrated similar outcomes between these two methods in patients with meniscal tears and minimal arthritis. This study explores factors influencing a patient's decision to choose operative versus nonoperative management in the treatment of nonarthritic meniscal lesions. Methods: Semistructured interviews were conducted with patients ages 18 to 50 yr old, with MRI confirmed diagnosis of meniscal tear and minimum of 2-year follow-up. Patients with Kellen-Lawrence Grade 2 or greater, with prior knee injuries, or knee surgeries were excluded. Qualitative analysis was performed to derive codes, categories, and themes. An assessment of patient-reported outcomes including the Knee Injury and Osteoarthritis Outcome Score (KOOS) and Marx activity score was also conducted. Results: Twenty-four patients with meniscal tears were interviewed. Those who chose surgical management with arthroscopic partial meniscectomy (n=12) cited significant pain, desire for definitive treatment, and aggressive personality traits. The nonoperative group (n=12) frequently had social constraints precluding surgery, more conservative personalities, and symptoms that did not affect their daily lives. The nonoperative group had significantly lower KOOS scores in symptoms (90.2 vs. 76.5, P =0.05), sports and recreation (84.2 vs. 64.2, P =0.05), and quality of life (QOL) (85.4 vs. 62.0, P =0.01). Conclusions: Psychological and social factors such as pain perception, personality, and time commitments affected patients' decisions to undergo surgical or conservative management for meniscal tears. This study may help surgeons and other health care professionals better understand and educate patients contemplating surgery. Level of Evidence: Level IV.